DIGITAL BRANDING STRATEGY ON MSME PRODUCTS IN THE ERA OF THE COVID-19 PANDEMIC - Edwin Zusrony; Indra Ava Dianta; Dewi Widyaningsih; Agustinus Budi Santoso (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The Covid-19 pandemic has hit the business world where this pandemic has greatly reduced people's purchasing power. The implementation of Community Activity Restrictions (PPKM) in the Java and Bali regions has resulted in a significant decrease in sales turnover and income for MSME actors. This study has the aim of implementing a digital branding strategy through social media such as YouTube to increase product sales of MSME actors in Boyolali district, Central Java. The researcher took a case study of the Angkringan Joglo Boyolali UMKM which is located in the Mojosongo sub-district as the object of research. The method used in this research is descriptive quantitative with data collection using several ways including: interviews, questionnaires, observation, documentation and literature study. Based on the implementation of the YouTube social media utilization strategy as well as the results of monitoring and evaluation measured from the results of the respondents' questionnaires (consumers), the results were obtained from the average visitor assessing the digital branding strategy of Angkringan Joglo Boyolali through social media such as YouTube giving answers strongly agree with a value above 60% based on indicators of personal branding dimensions (competence, style and standards). In the future, it is hoped that MSME players can enter the world of e-commerce to increase their business capacity as business partners.